The Personality of the Main Characters in Wacan Bocah by S. Wahyuni Adi: A Sigmund Freud Psychoanalytic Study - Fanya Fairus Azaria; Amanda Ningtiyas; Latif Nur Hasan; Meinita Istantiani (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2026)
Studies examining the personality structure of main characters in Javanese children's literature remain limited, particularly in revealing the psychological values embedded in children's stories. The study aims to analyze the main character’s personality in the wacan bocah Penulis Cilik and Nggawe Kebun Sayur by S. Wahyuni Adi, using Sigmund Freud’s psychoanalytic approach, which encompasses three elements of personality: the id, the ego, and the superego. The method used is a qualitative descriptive approach, employing data collection techniques such as literature reviews and documentation. The data were analyzed using content analysis. The data used included dialogue, narration, and character actions. The study's findings indicate that the id element is evident in the characters’ desires, such as their aspirations and their need to achieve self-satisfaction. The ego element reflects the characters’ ability to adapt to social situations. The superego element is evident through the influence of values related to discipline, ethics, and social responsibility. These findings indicate that S. Wahyuni Adi’s work not only offers stories for entertainment but also explores complex psychological dynamics relevant to children’s literature research. This study contributes to the development of literary psychology studies, particularly regarding the formation of children’s characters in Javanese-language literature.